Diversity and abundance of sea cucumber (Holothuroidea) resources in the Waters of Duroa Island, Tual City, Maluku, Indonesia - NENENG SUARNO KALIDI; MAX RUDOLF MUSKANANFOLA; SURYANTI SURYANTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kalidi NS, Muskananfola MR, Suryanti S. 2023. Diversity and abundance of sea cucumber (Holothuroidea) resources in the Waters of Duroa Island, Tual City, Maluku, Indonesia. Biodiversitas 24: 6002-6009. The people of Duroa Island, Tual City, Indonesia, have been utilizing sea cucumber resources continuously without considering its impact on ecological factors and sustainability. Formulating management initiatives is one possible solution to sustain the stock. However, it is hampered by the lack of information on its current status. This study aims to assess the abundance and diversity as well as the condition of the aquatic environment. In the observation 9 sea cucumbers were found from Holothuria, Bohadschia, Actinopyga, Stichopus, and Thelenota genera. The density of sea cucumber was highest at station 4 (0.417 ind/m²), and lowest at station 1 (0.083 ind/m²). Holothuria edulis dominated the sea cucumber community at a density of (0.450 ind/m2). Habitat characteristics of sea cucumber observation stations on Duroa Island are dominated by seagrass, rocky sand, rough sand, and sand. Ecological indices such as diversity are classified as moderate, high uniformity, and low dominance. All observation stations have water quality that is still in the optimal range according to water quality standards for marine biota, except at station 1 because the station has a pH value below the national quality standard of <6.5.